2007
DOI: 10.1073/pnas.0709276104
|View full text |Cite
|
Sign up to set email alerts
|

Poxvirus DNA primase

Abstract: Poxviruses are large enveloped viruses that replicate in the cytoplasm of vertebrate or invertebrate cells. At least six virus-encoded proteins are required for synthesis and processing of the doublestranded DNA genome of vaccinia virus, the prototype member of the family. One of these proteins, D5, is an NTPase that contains an N-terminal archaeoeukaryotic primase domain and a C-terminal superfamily III helicase domain. Here we report that individual conserved aspartic acid residues in the predicted primase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 47 publications
0
57
0
Order By: Relevance
“…Vaccinia virus genome uncoating follows a multistep process. First, the viral core becomes acid activated, probably in macropinosomes, and early genes are transcribed within the intact viral core (61). This mode of entry, related to endocytosis, could be somewhat inhibited by blocking cholesterol efflux.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinia virus genome uncoating follows a multistep process. First, the viral core becomes acid activated, probably in macropinosomes, and early genes are transcribed within the intact viral core (61). This mode of entry, related to endocytosis, could be somewhat inhibited by blocking cholesterol efflux.…”
Section: Discussionmentioning
confidence: 99%
“…VACV replication/ transcription occurs entirely in the cytoplasm of infected cells; therefore, the viral genome encodes the majority of viral proteins needed for this process, although some host ancillary proteins are recruited for intermediate and late gene transcription (110). A genome-wide Y2H screen showed that VACV A20 (DNA polymerase processivity cofactor) interacts with D4 (uracil DNA glycosylase), D5 (nucleic acid-independent nucleoside triphosphatase) (45), and H5 (DNA binding protein) (101). Furthermore, VACV A20 and D4 form a heterodimeric processivity factor by associating with E9 (catalytic subunit of the DNA polymerase holoenzyme) to comprise the processive DNA polymerase holoenzyme (157).…”
Section: Virus-virus Protein Interactionsmentioning
confidence: 99%
“…We had assumed that since poxviruses encode their own DNA primase (the VACV D5 protein exhibits a helicase-primase activity [127]), there would be no reason to expect that cellular PRIM2 would play any direct role in virus DNA replication. However, as a check on this assumption, we transfected cells with a plasmid carrying a myc-tagged version of PRIM2 (none of the available antibodies were suitable for use in imaging applications) and then monitored the distribution of the protein in mock-and MYXVinfected cells.…”
Section: Resultsmentioning
confidence: 99%